The importance of growing a pro-saving financial behaviour with an impact on the well-being of the individual. Achieving financial independence - ideas and tips - Bilți, Raluca Simina; Sanda, Cristina Maria; Grapini, Ioan; Faur, Flaviu Casian (Technium Social Sciences Journal, 2022)
Along the last years, it has been increasingly observed that a reduced understanding of a pro-saving financial behaviour, the lack of financial literacy, have led to bad decisions regarding the living of an individual, of a family and finally, by extension, the well-being of a nation. The lack of financial literacy is also confirmed by surveys of various organizations, measuring the awareness of the population about interest, inflation, loans, etc., knowledge that seems to be very poor. People's negative habits have consequences, such as: accumulating debts, ,many times not even realizing how quickly this happens. This article aims to present a theoretical approach and some tips & tricks for saving up and offers some practical solutions.